Isolated anti-Ro52 identifies a severe subset of Sjögren’s syndrome patients - Lee, Adrian Y. S.; Putty, Trishni; Lin, Ming-Wei; Swaminathan, Sanjay; Suan, Dan; Chataway, Tim; Thurlings, Rogier M.; Gordon, Tom P.; Wang, Jing Jing; Reed, Joanne H. (Frontiers in Immunology, 2023)
Introduction: Serum autoantibodies targeting the SSA/Ro proteins are a key component of the classification criteria for the diagnosis of Sjögren’s syndrome (SS). Most patient serum reacts with both Ro60 and Ro52 proteins. Here we compare the molecular and clinical characteristics of patients diagnosed with SS with anti-Ro52 in the presence or absence of anti-Ro60/La autoantibodies. Methods: A cross-sectional study was performed. Patients in the SS biobank at Westmead Hospital (Sydney, Australia) that were positive for anti-Ro52 were included and stratified based on the absence (isolated) or presence (combined) of anti-Ro60/La, measured by line immunoassay. We examined clinical associations and the serological and molecular characteristics of anti-Ro52 using ELISA and mass spectrometry in serological groups. Results: A total of 123 SS patients were included for study. SS patients with isolated anti-Ro52 (12%) identified a severe serological subset characterised by higher disease activity, vasculitis, pulmonary involvement, rheumatoid factor (RhF) and cryoglobulinaemia. Serum antibodies reacting with Ro52 in the isolated anti-Ro52 subset displayed less isotype switching, less immunoglobulin variable region subfamily usage and a lower degree of somatic hypermutation than the combined anti-Ro52 subset. Conclusions: In our cohort of SS patients, isolated anti-Ro52 represents a severe subset of SS, and is associated with the presence of cryoglobulinaemia. We therefore provide clinical relevance to the stratification of SS patients by their sero-reactivities. It is possible that the autoantibody patterns may be immunological epiphenomena of the underlying disease process, and further work is required to unearth the mechanisms of the differential clinical phenotypes.